Hubungan Lingkar Lengan Atas (LILA) pada Ibu Hamil dengan Kejadian Berat Badan Lahir Rendah (BBLR): Systematic Review - Nisak, Siti Khoirotun; Nadhiroh, Siti Rahayu (Media Gizi Kesmas, 2024)
Background: Indonesia is recorded as having a fairly high incidence of maternal and infant mortality compared to other developing countries. The number of deaths of newborn babies in 2015 was 33,278 cases, down from 32,007 cases in 2015 and 10,294 cases in the first quarter of 2017. Low Birth Weight (LBW) cases were one of the factors that led to infant deaths, amounting to 38,85 % of cases occur in Indonesia. Babies experience LBW if their birth weight does not reach 2,500 grams. The occurrence of LBW can be controlled by the nutritional condition of pregnant women. Maternal nutritional status at risk of LBW cases can be measured using anthropometry, namely Mid-Upper Arm Circumference Measure (MUAC) and Body Mass Index (BMI). Pregnant women have a high risk if the MUAC number is <23.5 cm and BMI <18. Objectives: This literature study was conducted to analyze the influence of pregnant women's Mid-Upper Arm Circumference Measure (MUAC) on the risk of LBW. Methods: This article was written using a systematic review method. The data sources for the articles were obtained from Science Direct literature articles, PubMed, Google Scholar and 10 relevant articles were obtained. Articles are limited to original research used with publication years 2017 to 2022. Results: Exposure to infectious and non-infectious diseases can worsen the effects of malnutrition on pregnant women and the fetus they are carrying, thus having an impact on the occurrence of LBW. which is 20 times compared to the birth of a baby with ideal body weight. Conclusions: This review concludes that MUAC of pregnant women has a strong relationship with LBW problems.